Strengthening the Creativity of Junior High School Teachers Through the Integration of Immersive Virtual Spaces in Interactive Learning - Rahmatiah, Rahmatiah (IJBLE Scientific Publications Community Inc., 2023)
This community service initiative was designed with three primary objectives: (1) to enhance the creativity and teaching competencies of teachers and educational staff at SMP PGRI 12 Jakarta; (2) to improve teaching performance through the utilization of immersive virtual space technologies; and (3) to expand the pedagogical insights of educators by integrating immersive virtual environments into the learning process. The program was implemented in three distinct phases: preparation, implementation, and evaluation. A total of 30 participants engaged in the program, demonstrating high levels of enthusiasm and active participation. Preliminary assessments and discussions with the partner institution revealed several challenges, primarily related to the suboptimal use of digital technologies in classroom settings. Although educators had adopted basic tools such as Zoom, Google Meet, and Google Classroom, the transition to more advanced digital platforms required by Industry 5.0 remains inadequate. Many teachers appeared unprepared for the rapidly evolving technological landscape. As a response, this initiative introduced immersive virtual space technologies—particularly through metaverse-based learning platforms—as innovative tools to support and enhance interactive learning. The training facilitated a shift in perception among the teachers, who began to recognize the importance and potential of immersive technology in future education. The program successfully demonstrated that metaverse integration can significantly contribute to creative, effective, and engaging pedagogical practices.